The Effect of Poisoning Level of Feed Given to Mulberry Silkworm on Larvae Survival and Colon Productivity - Bekkamov Chorshanbi Ismailovich; Mirzayeva Yorkinoy Yarkulovna (Zien Journals, 2022)
The causes, symptoms, diagnosis and prevention of diseases caused by the poisoning of the leaves of mulberry trees, which give special nutrients to different agricultural crops during the agrotechnics of mulberry silkworm care during the agrotechnics of mulberry silkworm care by farms, clusters and homesteaders in our republic. It is intended to achieve high-quality cocoon cultivation by saving larvae by applying measures.
Keywords: egg; larva; hatchery; worm feeding